2017
DOI: 10.1016/j.jbtep.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A client-level session-by-session evaluation of behavioral activation’s mechanism of action

Abstract: Background and Objectives Our understanding of how Behavioral Activation (BA) for depression works is limited. BA is theorized to lead to changes in depression through changes in activation. While distal support for activation as a mechanism has been obtained, more research is needed before definitive conclusions can be drawn. Research on mechanism should consider the appropriate time-frame for examining changes in the theorized mechanism variable and whether the proposed mechanism is expected to exert causal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 62 publications
1
11
0
2
Order By: Relevance
“…This has been demonstrated in a recent small scaled study that found that changes in activation preceded or co-occurred with changes in depression in adults, while in TAU this pattern was not found [39]. Another potential therapy-specific mechanism of BA is rumination.…”
Section: Mechanisms Predictors and Moderatorsmentioning
confidence: 89%
“…This has been demonstrated in a recent small scaled study that found that changes in activation preceded or co-occurred with changes in depression in adults, while in TAU this pattern was not found [39]. Another potential therapy-specific mechanism of BA is rumination.…”
Section: Mechanisms Predictors and Moderatorsmentioning
confidence: 89%
“…Despite initial evidence supporting the temporal relationship between activation and changes in depression symptom scores, further research is needed to fully elucidate the relationship between changes in BA and changes in symptoms. Specifically, questions remain related to the appropriate time frame required to evaluate the impact of activation and dose of BA treatment needed to make this claim (Santos et al, 2017). Temporal links between activation, reward, and changes in anhedonic symptoms may be further clarified with objective ratings of activation as well as proximal measures (Santos et al, 2017), such as momentary time sampling and electronic monitoring tools (e.g., Global Positioning System [GPS], pedometer).…”
Section: Behavioral and Symptom-specific Measuresmentioning
confidence: 99%
“…In that study, availability of potential rewards at baseline predicted depressive symptoms 8 months later, an effect that was mediated by self-reported BA levels 4 months after baseline assessment. A separate study by Santos and colleagues (2017) evaluated activation and depression symptom data from an RCT comparing BA with TAU in a population of Latino immigrants. Using cross-lagged correlation analyses, results showed that the vast majority of clients receiving BA (79%) demonstrated a pattern wherein changes in activation preceded or co-occurred with changes in depression symptoms, yet no clients in the TAU condition evidenced this pattern.…”
Section: Activation As the Mechanism Of Change In Bamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, changes in activity preceded depression reduction by 2 weeks in a small study (Santos et al, ), and BA predicted the decrease of depressive symptoms after 4 months (Hill, Buitron, & Pettit, ). In line with this, therapeutic compliance—operationalized as assigned activities—was positively related to subsequent depression reduction in breast cancer patients treated with BA (Ryba et al, ); however, this effect could not be shown when quantitative measures of activities were used.…”
Section: Introductionmentioning
confidence: 97%